Atividade reprodutiva de Plagioscion squamosissimus (Heckel,1840) (Actinopterygii,Perciformes), no reservatório de Pedra, Rio de Contas, Bahia - FÉLIX, Renata Triane da Silva (2008)
We evaluated the reproductive aspects of the organization and characterization of oocytes and the maturational stages of Plagioscion squamosissimus in the reservoir of stone, river of Auditors, Bahia. The collections were bimonthly, conducted between november/04 and september/06. It was recorded during reproductive activity every year, with peaks in march/05 and from july/06. The average total fertility rate was 22,610 oocytes and fertility on the length was higher than the fertility on the weight when the standard length was more than 212mm. The proportion sexual presented significant difference (p <0.05) for the months of January, May, July and september/05 and, for the second year, a significant difference occurred in January and march/06. There was a concentration of lengths in modal class of 120 to 240mm for males and females in Year 1 and 2 males occurred in the larger class size. The weight-length relationship had reversed values for males and females in two years, registering for females increase in year 1 allometric negative and positive in year 2. The split was considered spawning and size of the first maturity was 150 for males and females. The GSR and the condition factor (allometric) when compared showed reverse in almost every period. The microscopic analyses were made through cuts in histology stained with hematoxylin-eosin-phloxine and mixture of Gomori’s tricromic. The gonads showed differentiation of color under the cages, suggesting a classification of cages. Through the macro and microscopic analysis identified five maturational stages. For the development oocitário, were defined six phases: oogonia and perinucleolus; vitelogenic and initial lipid; vitelogenic and lipid intermediate and advanced lipid vitelogenic and pre-ovulation. It was observed structures similar to that of marine fish, as droplets of oil in the final stages and a tendency to hydration pre-ovulatory. This is explained by the family seafood Sciaenidae, suggesting more detailedstudies to define these structures and stages of development ovocity. Despite the species to be well adapted to the environment, spawning the central body of the tank, it is necessary to enlarge the studies in this place, to establish parameters that will influence in its mechanism reprodutivo.Observou up structures similar to that of marine fish . As droplets of oil in the final stages and a tendency to hydration pre-ovulatory. This is explained by the family seafood Sciaenidae, suggesting more detailed studies to define these structures and stages of development ovocity.